Green finance and industrial pollution: Empirical research based on spatial perspective - Zhang, Lechao; Mei, Zihan (Frontiers in Environmental Science, 2022)
Green finance is an important means to promote industrial pollution reduction. This paper uses the entropy method and the TOPSIS model to calculate the green finance development index and industrial pollution index of 30 provinces in China from 2011 to 2019, and further uses the panel regression model and SDM model to test the impact of green finance on industrial pollution. The study found that there is a significant positive spatial correlation between green finance and industrial pollution; At the same time, green finance generally inhibits industrial pollution. The effect decomposition results show that the former has a significant negative direct effect and spatial spillover effect on the latter.